2021
DOI: 10.1002/jsfa.11668
|View full text |Cite
|
Sign up to set email alerts
|

UV‐C treatment inhibits browning, inactivates Pseudomonas tolaasii and reduces associated chemical and enzymatic changes of button mushrooms

Abstract: BACKGROUND Button mushrooms with completely white appearance are popular with consumers. However, button mushrooms are susceptible to infection with Pseudomonas tolaasii, which results in browning. This study evaluates the effects of ultraviolet‐C (UV‐C) treatment on the inactivation of P. tolaasii in vitro and in vivo and on the physiological and chemical changes of button mushrooms during storage for 21 days at 4 °C. RESULTS UV‐C doses of 0.5 to 9.0 kJ m−2 resulted in 3.91–6.26 log CFU mL−1 reduction of P. t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(104 reference statements)
1
12
0
Order By: Relevance
“…This finding was in agreement with our previous research that a reduction of PPO activity can cause an elevation in the accumulation of GHB and GDHB. 5 Our examination also revealed that UV-C-treated button mushrooms maintained a greater degree of whiteness. UV-C improved the antioxidant properties of button mushrooms TPC and PAL activity of button mushrooms According to reports, the primary non-enzymatic antioxidant components of mushrooms are phenolic compounds, which have a crucial function as ROS scavengers.…”
Section: Uv-c Impact On Changes In Ghb Gdhb and Tyrosine Contents Of ...mentioning
confidence: 56%
See 4 more Smart Citations
“…This finding was in agreement with our previous research that a reduction of PPO activity can cause an elevation in the accumulation of GHB and GDHB. 5 Our examination also revealed that UV-C-treated button mushrooms maintained a greater degree of whiteness. UV-C improved the antioxidant properties of button mushrooms TPC and PAL activity of button mushrooms According to reports, the primary non-enzymatic antioxidant components of mushrooms are phenolic compounds, which have a crucial function as ROS scavengers.…”
Section: Uv-c Impact On Changes In Ghb Gdhb and Tyrosine Contents Of ...mentioning
confidence: 56%
“…Our previous studies 5,10 found that UV-C irradiation at 1.0 kJ m −2 dose could not only achieve the desired germicidal effect but it could also better maintain the quality of A. bisporus during storage. Therefore, 1.0 kJ m −2 UV-C was selected in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations